2018
DOI: 10.21432/t2sq4w
|View full text |Cite
|
Sign up to set email alerts
|

Guitars and Makerspace: Examining the Experience of First Nations Students | Guitares et laboratoires ouverts : examen de l’expérience d’élèves des Premières Nations

Abstract: This research project examined the impact on student engagement of a makerspace approach in an all-First Nations high school. First Nations learners have many factors limiting their success in the K-12 system such as lack of connection to the curriculum, limited cultural relevance of course content, and poor attendance. A common concern for those working with First Nations students is how to deliver a learning experience that is engaging and assists students in earning enough credits to graduate. In this case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…As a result, research has shown that educators face a number of challenges when leading maker-based activities including the need to balance structure with student autonomy (Kajamaa et al, 2019;Rowsell & Shillitoe, 2019). A number of specific aspects that may be important for future teacher professional development include providing adequate structure for learning, embracing a culture of failure, effective preparation and planning, learning how assess problem based learning, and acknowledging the pedagogical value of maker based activities (Cohen et al, 2017;Kajamaa et al, 2019;O'Brien et al, 2017;Paganelli et al, 2017;Wilson & Gobeil, 2017). In one specific example, researchers observed 94 elementary students who participated in a weekly educational makerspace over one semester (Kajamaa et al, 2019).…”
Section: Teachers' Perceptions and Experiences Of Makerspacesmentioning
confidence: 99%
“…As a result, research has shown that educators face a number of challenges when leading maker-based activities including the need to balance structure with student autonomy (Kajamaa et al, 2019;Rowsell & Shillitoe, 2019). A number of specific aspects that may be important for future teacher professional development include providing adequate structure for learning, embracing a culture of failure, effective preparation and planning, learning how assess problem based learning, and acknowledging the pedagogical value of maker based activities (Cohen et al, 2017;Kajamaa et al, 2019;O'Brien et al, 2017;Paganelli et al, 2017;Wilson & Gobeil, 2017). In one specific example, researchers observed 94 elementary students who participated in a weekly educational makerspace over one semester (Kajamaa et al, 2019).…”
Section: Teachers' Perceptions and Experiences Of Makerspacesmentioning
confidence: 99%